Fire as a pre-emptive evolutionary trigger among seed plants - Lamont, Byron; He, Tianhua; Yan, Z. (Elsevier GmbH - Urban und Fischer, 2019)
© 2018 Elsevier GmbH There is mounting evidence that much of the world's vegetation has been fire-prone since the Upper Cretaceous, taking precedence over Cenozoic drought as a key agent of selection in the evolution of specialized traits adaptive to environmental stresses that otherwise result in species extinction. This raises the question of when the advent of surface fires occurred compared with the introduction of other critical selective agents, such as frost, seasonal drought, crown fire, nutrient-impoverished soils, new habitat types, and novel pollinators, herbivores and dispersal agents. Of particular interest is the relative time of origin of traits associated with fire-free habitats that traditionally have been viewed as ancestral. We collated 47 paired time sequences for a wide range of clades most of whose species are fire-prone. The objective was to determine the order of origin of fire-related traits relative to the origin of other fire-related traits associated with different fire regimes or non-fire-related traits in response to selective agents unrelated to fire. The results show that the initiation of fire-related traits in response to moderate fires (trigger 1) preceded either a) other fire-related traits that represent responses to an increase in the intensity or frequency of fire (trigger 2) (10 comparisons), b) traits associated with fire-free habitats (12 comparisons), or c) novel traits associated with selective agents unlinked to fire, with the fire-related traits now stabilized (25 comparisons). The only exception was the presence of ectomycorrhizas among pines, which are diagnostic for Pinaceae, suggesting that adaptations to poor soils occurred before this highly fire-prone genus evolved. For some early traits, there was confounding with several possible key selective agents apparently acting concurrently, although fire was always present, and these await further clarification. We conclude that fire has had a pre-emptive role in shaping many specialized traits fundamental to plant survival among fire-prone clades and that other selective agents, such as summer drought, have had a secondary role in promoting the evolution of additional novel traits that increased fitness in more recent times.